Complicacoes respiratorias em criancas submetidas a anestesia geral - Nascimento P., Jr [UNESP]; Neves, L. B J [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Gifoni, C. L. [UNESP] (My University, 2000)
Background and Objectives - The decision to perform anesthetic and surgical procedures in children with upper airway infeccious disease, due to the possibility of intraoperative respiratory morbidity, has been a dilemma for anesthesiologists. This study aimed at evaluating the incidence of respiratory complications in children submitted to general anesthesia and correlate them to preoperative signs and symptoms related to the respiratory tract, thus determining anesthetic-surgical morbidity. Methods - Participated in this study 284 children, physical status ASA I or II, submitted to general anesthesia. During preoperative evaluation, respiratory signs and symptoms were recorded, as well as types of diseases and corresponding diagnoses. Respiratory complications during anesthesia and in the recovery room were also recorded and analyzed taking into account age, elective or urgent procedure, airway management and presence or absence of signs, symptoms or history of respiratory tract diseases. Results - We found 38% of patients with preoperative respiratory disease history. The most common respiratory disease was upper airway infection. Intraoperative respiratory complications were present in 26.4% of patients. Children under 12 months of age and those with preoperative respiratory disease history had more intraoperative and PACU complications. Conclusions - We concluded that children, specially younger, with respiratory system involvement, like upper airway infections, are at a higher risk of intra and postoperative respiratory complications, thus with an increased incidence of anesthetic-surgical morbidity.
Respiratory complications in children submitted to general anesthesia
Keywords: Anesthesia: Pediatric; Complications: bronchospasm, hypoxia, laryngospasm, respiratory; bronchospasm; child; female; general anesthesia; high risk patient; human; infant; larynx spasm; major clinical study; male; pediatric anesthesia; postoperative complication; preoperative evaluation; upper respiratory tract infection